Kaiser and Führer : a comparative study of personality and politics - Waite, Robert G. L. (Robert George Leeson), 1919-1999 (University of Toronto Press, 1998)
Thoroughly documented and engagingly written this is a classic work of scholarship that will fascinate historians, psychologists, and general readers alike.